THE EFFECT OF SPONSORSHIP ON BRAND AWARENESS GRAB AT THE EVENT 18TH ASIAN GAMES - ZULFIKRI ZULFIKRI (Cross-Border Journal of Business Management, 2021)
This study aims to find out the effect of Sponsorship on Brand Awareness Grab At the Event 18th Asian Games. The data used in this study are primary data obtained from respondents through questionnaire questionnaires. The results showed that Sponsorship significantly influences Brand Awareness Grab At the 2018 Asian Games event with a sig value. t by (α) = 0.000 < 0.05 or 5%, so Ho was rejected and Ha accepted. This indicates that if there is an increase in sponsorship it will increase Grab's brand awareness, and vice versa if there is a decrease in sponsorship it will have an impact on the decline of Grab's brand awareness. Research is expected to be a reference for further research to add insight and knowledge in the field of marketing management, especially variables related to sponsorship and brand awareness. For Grab companies to improve themselves and respond to marketing methods through sports sponsorship that has been done to achieve the target as expected to improve the quality of the company.